Reducing the plight of migrant workers affected by COVID-19 - Khatiwada, Padma Prasad (Nepal Public Policy Review, 2021)
Since the start of the pandemic one and a half years ago, a precarious economic crisis has developed in the country due to the fluctuation in remittance, which had once contributed to nearly one-third of the total GDP. In the initial phase of the pandemic, around 1.5 million migrant workers were expected to return home by losing jobs in major destinations – India, the Middle East and Malaysia – which have over one-fifth of the total migrant workers abroad. On this backdrop, this paper highlights the situation of the Nepali migrant people in the destination during the time of the COVID-19 crisis. The paper utilises existing literature collected through various sources and explores possible areas of intervention. It aims to unpack the impact of the pandemic on migrant workers, remittance flows and the livelihoods of the migrant workers and their family members. The paper concludes that the rate of return may further upsurge depending upon the situation of the spread of the pandemic. The impact of the virus is not limited to a national economy. It is felt by every individual who has lost their jobs, their hopes of getting involved in new jobs and is left unattended by state authorities. Those involved in the informal sectors, particularly the women and those from marginalised communities, are left in a state in which they cannot feed their families and pay their rent due to the effect of lockdowns. To reduce the impact of the pandemic on migrant workers, both the government and non-government development partners must involve in the early recovery work aimed at generating information on the impact of COVID-19 and concentrating on the immediate priorities of those impacted. The priorities should be set based on the current living condition, by utilising best practices available and undertaking measures made up of the capsule of identification, awareness, organisation, putting the victims first and uncompromised monitoring for possible areas of intervention in local communities. These strategies should aim for reintegration by adopting the principle of informed choice of the workers.